Factors determining the oral absorption and systemic disposition of zeaxanthin in rats: in vitro, in situ, and in vivo evaluations. (31st December 2022) - Seo, Seong‑Wook; Han, Dong‑Gyun; Choi, Eugene; Seo, Min‑Jeong; Song, Im‑Sook; Yoon, In‑Soo
Abstract: Context: Zeaxanthin is a yellow‑coloured dietary carotenoid widely recognized as an essential component of the macula. It exerts blue light filtering and antioxidant activities, offering eye health and vision benefits. Objective: This study explores the oral absorption and systemic disposition of zeaxanthin from biopharmaceutical and pharmacokinetic perspectives. Materials and methods: In vivo intravenous (5 and 10 mg/kg) and intraportal (5 mg/kg) pharmacokinetic studies were performed to determine intrinsic tissue‑blood partition coefficient, elimination pathway, and hepatic clearance, of zeaxanthin in rats. Moreover, in vitro physicochemical property test, in situ closed loop study, in vivo oral pharmacokinetic study (20 and 100 mg/kg), and in vivo lymphatic absorption study (100 mg/kg) were conducted to investigate the gut absorption properties of zeaxanthin and assess the effects of several lipids on the lymphatic absorption of zeaxanthin in rats. Results: Zeaxanthin exhibited poor solubility (≤144 ng/mL) and stability (6.0–76.9% of the initial amount remained at 24 h) in simulated gut luminal fluids. Gut absorption of zeaxanthin occurred primarily in the duodenum, but the major fraction (≥84.7%) of the dose remained unabsorbed across the entire gut tract. Considerable fractions of intravenous zeaxanthin accumulated in the liver, lung, and spleen (21.3, 11.7, and 2.0%, respectively). It was found that the liver is the major eliminating organ of zeaxanthin, accounting for 53.5–90.1% of the total clearance process (hepatic extraction ratio of 0.623). Discussion and conclusions: To our knowledge, this is the first systematic study to report factors that determine the oral bioavailability and systemic clearance of zeaxanthin.